A very short, fairly interesting and reasonably cheap book about qualitative research - Silverman, David, 1943- (Los Angeles : ndonlo : SAGE, 2013)
"David Silverman's second edition provides a refreshing introduction to doing and debating qualitative research. An antidote to the standard textbook, this new edition shows how research can be methodologically inventive, empirically rigorous, theoretically-alive and practically relevant. Using materials ranging from photographs to novels and newspaper stories, the book demonstrates that getting to grips with qualitative methods means asking ourselves fundamental questions about how we are influenced by contemporary culture. By drawing on examples from websites and social media in the new edition, Silverman's text acknowledges how our social worlds are changing and explores new arenas for data collection. A new Glossary of Received Ideas aims to challenge conventional understandings of terms central to qualitative research and will inform, amuse and stimulate readers. This book is perfect pre-course reading for those new to research as well as seasoned researchers who want to reflect on their practice."--Publisher's website.
Introduction to the Second Edition -- Preface: Making a Space for This Book -- Innumerable Inscrutable Habits: Why Unremarkable Things Matter -- On Finding and Manufacturing Qualitative Data -- Instances or Sequences? -- Applying Qualitative Research -- The Aesthetics of Qualitative Research: On Bullshit and Tonsils -- A Very Short Conclusion -- A Glossary of Received Ideas -- Transcription Symbols.
Previous ed.: 2007.
Includes bibliographical references (p. [162]-169)-and indexes.
Keywords: Qualitative research; Social sciences -- Research; Qualitative research; Social sciences -- Research